Половые различия в проявлении агрессивности и эмпатии у жителей украинского мегаполиса - Лучко, Е.Н. (Фактори експериментальної еволюції організмів, 2014)
Aims. Studying of biological sleep of aggression and empathy is an important question because deviation of personal characteristics in this or that way may lead to different psychic states. In turn, people, suffering psychopathy, are able to show unsocial behavior (crime, violence, etc). Lack of information about the link between aggression and empathy in Ukrainian population restrains the further genetic analysis of these characteristics. Methods. 1493 Kharkiv citizens aged 45–65 (637 males and 856 females) took part in the studying. The Assinger’s questionnare was used to estimate aggression, the Megrabyan – Epstein’s questionnare was used to estimate empathy. Results. The empathy and aggression level in males and females aged 45–65 does not depend on age. The average male aggression point is higher than the female one. As for empathy males also exceed females. Conclusions. Such personal characteristics as aggression and empathy do not depend on age which does not mean that formation of those personal characteristics are not influenced by social status, upbringing, demographic status and genetic factors. In our population males are more aggressive than females. At the same time males are more apt to empathy than females.